PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI DAN KOMPENSASI FINANSIAL TERHADAP KINERJA KARYAWAN - NURTI WIDAYATI (Media Bisnis, 2016)
The purpose of this research is to determine and analyze the influence of Transformational Leadership Style, Communication and Financial Compensation towards Employee’s Performance. Data used in this research were collected from 197 employees which selected by Purposive Sampling. Samples were selected based on the criteria. In this research, researcher used Simple Regression Analysis and Multiple Regression Analysis to analyze the data. The Results of this research, by partially showed that each Independent Variables such as Transformational Leadership Style, Communication and Financial Compensation are influence toward Employees Performance.